2006
DOI: 10.1002/bjs.5300
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of thrombophilia in patients with symptomatic peripheral vascular disease

Abstract: A quarter of patients with peripheral vascular disease had evidence of thrombophilia, and a third had hyperhomocysteinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…By using genetic tests as standard in the considered population, the overall prevalence of FVL carriers was 42.5%, the prevalence of homozygous patients was 4.5%. These results were higher than the prevalence reported in literature in patients with VTE (Vig et al, 2006).…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…By using genetic tests as standard in the considered population, the overall prevalence of FVL carriers was 42.5%, the prevalence of homozygous patients was 4.5%. These results were higher than the prevalence reported in literature in patients with VTE (Vig et al, 2006).…”
contrasting
confidence: 77%
“…Nevertheless the more usual diagnostic approach is the use of functional screening tests. Even in a selected series like the group of patients considered in this study, only a minority showed genetic defects (De Stefano et al, 2002;Vig et al, 2006). Genetic tests are much more expensive and labour intensive than any clot based screening assay (65 vs. 5 Euro/test) (Gessoni et al, 2007).…”
mentioning
confidence: 94%
“…There have been many reports showing the association between hypercoagulability and development or progress of atherosclerotic vascular disease. [6][7][8][9] Vig et al 10 reported that a quarter of patients with PAD had evidence of thrombophilia. In their other review article, 11 the risk of thrombotic occlusion following arterial revascularization in patients with an identified thrombophilia defect appeared to be almost 3 times that in patients without it.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet neutralization procedure in the DRVVT was found in 26 out of the 60 (43%) vascular patients compared with none of the 20 general surgical controls [30], though a later survey found a lower 4% prevalence of LA in 150 patients with peripheral vascular disease [31].…”
Section: Peripheral Vascular Disease and Antiphospholipid Antibodiesmentioning
confidence: 98%